Hate groups targeting unauthorized immigrants: discourses, narratives and subjectivation practices on their websites - Gemignani, Marco; Hernandez-Albujar, Yolanda (Ethnic and racial studies, 2015)
The narratives and images on websites of US hate groups that oppose undocumented immigrants represent and reproduce discourses that contribute to the subject formation of group members, who feel ethically obliged to counter unauthorized immigration. Left alone by the government, which is seen as unreliable and uncaring of patriotic values, they position themselves as heroic saviours of the nation. We argue that these hate groups' 'games of truth' develop in response to the perception that irregular immigration threatens specific social orders and values, for instance about citizenship, national identity and otherness. This article helps to understand the ways in which anti-immigrant narratives serve the functions of countering these threats and of asserting the group members' ethical obligation as a form of care of the self. In other words, from a Foucaultian viewpoint, we interpret the problematizations of 'illegal' immigration as discursive practices for the subject formation of hate group members.